2013
DOI: 10.5489/cuaj.325
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal clonidine added to small-dose bupivacaine prolongs

Abstract: Introduction: The aim of this prospective, double-blinded study was to investigate the effects of clonidine in co-administration with bupivacaine during spinal anesthesia, regarding the onset and regression of motor and sensory block, postoperative analgesia and possible side effects. Methods: We randomly selected 66 male patients (age 35 to 70), from the American Society of Anesthesiologists (ASA) class I-II; these patients were scheduled for transurethral surgical procedures. These patients were randomly all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…We found the time of onset of sensory and motor blockade to be significantly less in patients who were given intrathecal clonidine. Similar results were observed by Strebel et al, 8 and Gecaj-Gashi et al, 9 who reported shorter onset of sensory and motor block in patients receiving intrathecal clonidine.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found the time of onset of sensory and motor blockade to be significantly less in patients who were given intrathecal clonidine. Similar results were observed by Strebel et al, 8 and Gecaj-Gashi et al, 9 who reported shorter onset of sensory and motor block in patients receiving intrathecal clonidine.…”
Section: Discussionsupporting
confidence: 88%
“…This could be explained by adequate preloading which was performed in all the patients prior to subarachnoid block. In addition, the dose used in our study was small (30 μg), and the mean level of anaesthesia achieved was T [8][9] . Our results are similar to those of Singh et al who observed no significant difference in HR and blood pressure in patients receiving 30 μg and 50 mcg of clonidine intrathecally undergoing cesarean section 13 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lower doses of intrathecal bupivacaine caused a reduction in the number of blocked dermatomes, and the duration of SA was reported. The co-administration of other adjuvant drugs can reduce the required bupivacaine dose and improve the quality of SA [3]. Several studies have reported improved surgical outcomes by including fentanyl, a lipophilic opioid, in spinal anesthesia [6,[14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…It is the first and standard choice for many urological surgeries. It is also commonly used in transurethral surgeries, making it easy to detect the symptoms of overhydration, bladder perforation, and transurethral resection of prostate (TURP) syndrome [3]. There is a tendency to perform transurethral lithotripsy (TUL) with SA due to fewer complications than general anesthesia [2,4].…”
Section: Introductionmentioning
confidence: 99%